Strategi Kreatif Liga Dangdut Indosiar Episode Kemenangan - Andreas Tjandra; Syaifuddin (UNIVERSITAS KALBIS, 2022)
This study explores the creative strategy of Liga Dangdut Indonesia 2019 talent search program. The research approach used in this research is a qualitative research approach with a post-positivism paradigm and a descriptive type of research. The analysis technique used is the SWOT analysis to determine the creative strategies used by Liga Dangdut Indonesia 2019 production team. The data collection technique that the researchers used was in-depth interviews with four informants. The results of this study show that there are many strategies used in Liga Dangdut 2019 Episode Kemenangan, such as providing long-duration shows, various variations of dangdut songs, various kinds of gimmicks displayed by the host and the jury, participants taken from all provinces in Indonesia, broadcast time in prime time hours, and an interesting selection of guest stars.